ROA, ROE, and EPS on Stock Prices in The Basic & Chemical Industry Sector Listed on The Jakarta Composite Index - Sonia Krisdayanti (Indonesian Financial Review, 2021)
This study aims to examine the effect of Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS) on Stock Prices in Manufacturing Companies in the Basic & Chemical Industry Sector Listed on the Indonesia Stock Exchange (IDX) for the 2015-2019. The sample selection in this study used purposive sampling method. The method used in this research is panel data regression analysis. The results of the research are: Return on Assets (ROA) has no a significant effect on stock prices. This is indicated by the t-count is greater than the t-table value (1.009 < 1.98), with a probability value bigger than the significance or (0.3151 > 0.05), while the Return On Equity (ROE) has no significant effect on the price share. This is indicated by the t-count is smaller than the t-table value (0.849 < 1.98), with a probability value greater than significance or (0.3978 > 0.05), then Earning Per Share (EPS) has a significant effect on stock prices. This is indicated by the t-count is greater than the t-table value (2.16  > 1.98), with a probability value smaller than the significance or (0.0331 < 0.05), and Based on the results of the F test, Return On Assets (ROA), Return On Equity (ROE) and Earning Per Share (EPS) together have a significant effect on stock prices. This is indicated by the F-count value is greater than the F-table (27.61 > 2.63), and the probability value is also smaller than the 0.05 significance level (0.0000 < 0.05).